Effects of Sex, APOE4, and Lifestyle Activities on Cognitive Reserve in Older Adults. (23rd August 2022) - Pa, Judy; Aslanyan, Vahan; Casaletto, Kaitlin B.; Rentería, Miguel Arce; Harrati, Amal; Tom, Sarah E.; Armstrong, Nicole; Rajan, Kumar; Avila-Rieger, Justina; Gu, Yian; Schupf, Nicole; Manly, Jennifer J.; et al.
Abstract : Background and Objectives: Lifestyle activities, such as physical activity and cognitive stimulation, may mitigate age-associated cognitive decline, delay dementia onset, and increase cognitive reserve. Whether the association between lifestyle activities and cognitive reserve differs by sex and APOE4 status is an understudied yet critical component for informing targeted prevention strategies. The current study examined interactions between sex and physical or cognitive activities on cognitive reserve for speed and memory in older adults. Methods: Research participants with unimpaired cognition, mild cognitive impairment, or dementia from the Washington Heights-Inwood Columbia Aging Cohort were included in this study. Cognitive reserve scores for speed and memory were calculated by regressing out hippocampal volume, total gray matter volume, and white matter hyperintensity volume from composite cognitive scores for speed and memory, respectively. Self-reported physical activity was assessed using the Godin Leisure Time Exercise Questionnaire, converted to metabolic equivalents (METS). Self-reported cognitive activity (COGACT) was calculated as the sum of 3 yes/no questions. Sex by activity interactions and sex-stratified analyses were conducted using multivariable linear regression models, including a secondary analysis with APOE4 as a moderating factor. Results: Seven hundred fifty-eight participants (mean age = 76.11 ± 6.31 years, 62% women) were included in this study. Higher METS was associated with greater speed reserve in women (β = 0.04, CI 0.0–08) but not in men (β = 0.004, CI −0.04 to 0.05). METS was not associated with memory reserve in women or men. More COGACT was associated with greater speed reserve in the cohort (β = 0.13, CI 0.05–0.21). More COGACT had a trend for greater memory reserve in women (β = 0.06, CI −0.02 to 0.14) but not in men (β = −0.04, CI −0.16 to 0.08). Only among women, APOE4 carrier status attenuated relationships between METS and speed reserve (β = −0.09, CI −0.22 to 0.04) and between COGACT and both speed (β = −0.26, CI −0.63 to 0.11) and memory reserves (β = −0.20, CI −0.50.0 to 093). Discussion: The associations of self-reported physical and cognitive activities with cognitive reserve are more pronounced in women, although APOE4 attenuates these associations. Future studies are needed to understand the causal relationship among sex, lifestyle activities, and genetic factors on cognitive reserve in older adults to best understand which lifestyle activities may be most beneficial and for whom.